A novel conjugal donor strain for improved DNA transfer into Clostridium spp. (October 2019) - Woods, Craig; Humphreys, Christopher M.; Rodrigues, Raquel Mesquita; Ingle, Patrick; Rowe, Peter; Henstra, Anne M.; Köpke, Michael; Simpson, Sean D.; Winzer, Klaus; Minton, Nigel P.
Abstract: Clostridium encompasses species which are relevant to human and animal disease as well as species which have industrial potential, for instance, as producers of chemicals and fuels or as tumour delivery vehicles. Genetic manipulation of these target organisms is critical for advances in these fields. DNA transfer efficiencies, however, vary between species. Low efficiencies can impede the progress of research efforts. A novel conjugal donor strain of Escherichia coli has been created which exhibits a greater than 10-fold increases in conjugation efficiency compared to the traditionally used CA434 strain in the three species tested; C. autoethanogenum DSM 10061, C. sporogenes NCIMB 10696 and C. difficile R20291. The novel strain, designated 'sExpress', does not methylate DNA at Dcm sites (CCWGG) which allows circumvention of cytosine-specific Type IV restriction systems. A robust protocol for conjugation is presented which routinely produces in the order of 10 5 transconjugants per millilitre of donor cells for C. autoethanogenum, 10 6 for C. sporogenes and 10 2 for C. difficile R20291. The novel strain created is predicted to be a superior conjugal donor in a wide range of species which possess Type IV restriction systems. Highlights: A novel conjugal donor strain has been constructed to circumvent Type IV restriction. Improved DNA transfer to C. difficile R20291, C. sporogenes and C. autoethanogenum. A knockout strain of C. autoethanogenum exhibited ∼10× higher conjugation efficiency. A knockout strain of C. sporogenes exhibited ∼10× higher conjugation efficiency. Clostron mutant converted to in-frame deletion using CRISPR/Cas9. Abstract : Importance: The ability to transfer genetic material into a target organism is crucial for the development of a wide range of targeted genetic manipulation techniques. Overcoming the organisms' native restriction systems which target foreign incoming DNA is one strategy that can increase the efficiency of genetic transfer. The novel E. coli donor strain described here employs this strategy, increasing the frequencies of conjugation into a range of clostridial strains, and therefore opening up the potential to implement novel gene manipulation techniques. Furthermore this novel donor strain has potential applications across a wide range of genetically recalcitrant organisms, and should be beneficial wherever the frequently occurring Type IV restriction systems are possessed by the target in question.